Strategi sehat mengelola emosi negatif tanpa menyakiti diri sendiri - Lailiyah, Adhimah (Maliki Interdisciplinary Journal, 2025)
Negative emotions are a natural part of human life that often manifest as feelings of anger, sadness, disappointment, anxiety, or fear. If not managed properly, these emotions can have a detrimental effect on mental and physical health, as well as social relationships. This paper aims to provide an understanding and strategies for managing negative emotions in a healthy and constructive manner so that they do not develop into harmful behaviors, including self-harm. The method used is a literature review with a qualitative approach. The discussion reveals that emotion management can be achieved through three main approaches: psychological (such as deep breathing, meditation, and mindfulness), Islamic (through patience, prayer, remembrance of God, and trust in God), and social (by keeping a feelings journal and seeking social support). These three approaches complement each other in fostering a wiser response to emotional stress. With consistent application, individuals can enhance their emotional resilience and reduce the risk of self-destructive actions